2016
DOI: 10.1039/c6em00222f
|View full text |Cite
|
Sign up to set email alerts
|

Environmental transmission of diarrheal pathogens in low and middle income countries

Abstract: Every year, more than half a million children die due to diarrheal diseases. Recent studies have identified the most important etiologies of diarrheal disease are enterotoxigenic and enteropathogenic E. coli, Shigella spp., rotavirus, norovirus and Cryptosporidium spp. These etiologies are unsurprisingly characterized by a combination of high shedding, high infectivity, and transmissibility through multiple environmental reservoirs. The relative importance of the transmission routes is likely site-specific. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 138 publications
(205 reference statements)
3
102
0
Order By: Relevance
“…As a result, viral pathogens spread easily from person to person and via fomites [57,60,61]. Evidence suggests that improvements in sanitation alone are not sufficient to prevent enteric virus transmission [62], especially rotavirus which is highly infectious and extremely persistent in the environment [63]. Our results are consistent with research from India which reported an increased risk (though not significantly) of previous viral infection among urban households with toilets [64].…”
Section: Discussionsupporting
confidence: 85%
“…As a result, viral pathogens spread easily from person to person and via fomites [57,60,61]. Evidence suggests that improvements in sanitation alone are not sufficient to prevent enteric virus transmission [62], especially rotavirus which is highly infectious and extremely persistent in the environment [63]. Our results are consistent with research from India which reported an increased risk (though not significantly) of previous viral infection among urban households with toilets [64].…”
Section: Discussionsupporting
confidence: 85%
“…RVA affect children of all social classes, indicating that, unlike other enteric pathogens of fecal-oral transmission, improvements in basic sanitation and hygiene procedures seems to be not sufficient to control the virus infection (Barreto et al, 2006). RVA is persistent in environment and extremely infectious (ID50 is ~ 6 viral units) (Julian, 2016). Therefore, the most effective approach to control RVA infections is by vaccination (Estes & Greenberg, 2013).…”
Section: Population and Individual Control Measuresmentioning
confidence: 99%
“…Intestinal protozoan parasites are a major global health burden; giardiasis is an important parasitic cause and is accompanied by diarrhea …”
Section: Introductionmentioning
confidence: 99%
“…Intestinal protozoan parasites [4] are a major global health burden; giardiasis [5] is an important parasitic cause and is accompanied by diarrhea. [6][7][8] According to WHO, this insidious disease is the second-leading cause of death in child mortality and morbidity, a global urgency that cannot be overlooked.…”
mentioning
confidence: 99%